Failing at success: a Durkheimian analysis of anomie and deviant behavior among national football league players - Carter, Eric Michael (Kansas State University, 2006)
This exploratory research project has utilized a mixed-method (Seiber 1973; Creswell 1994, 2005; Jick 1979; Dexter 1970) approach to examine why some NFL players participate in deviant, and sometimes law breaking, behavior and others do not. Using Dexter’s (1970) qualitative technique of elite and specialized interviewing along with Schatzman’s and Strauss’s (1973) naturalistic field method, access was gained into an exclusive group of current and former NFL players. The qualitative findings in conjunction with Durkheimian theory provided the conceptualization of a quantitative instrument. Through a nonprobability snowball sample (Babbie 1986; Berg 2001), 104 NFL players were interviewed. A series of quantitative analyses were run to describe and assess relationships within this study group. In essence, this study has entailed a series of steps that could be represented as a cumulative progression. From the qualitative data, the three core themes that emerged were (1) deviance, (2) anomie, and (3) social ties. Within the study group, a substantial number of players had prior experience with deviant and illegal behaviors. Many reported problems coping upon entering the NFL and sought to find personal fulfillment and happiness despite wealth and fame. It appeared that some level of anomie was present in a number of these players’ lives. However, players that had strong ties to various social groups appeared less likely to succumb to anomie and deviance. Supporting the qualitative data, the quantitative findings revealed that anomie was one of the significant predictors of law breaking players. It would therefore appear reasonable to suggest that some of the players were involved in behaviors that could be labeled anomic deviance. Furthermore, the findings supported the primacy of social ties/support in combating anomie and deviance in the lives of NFL players in the study group.
Keywords: anomie; deviance; sport; Sociology, General (0626)